PEMILIHAN DOSEN TELADAN BERPRESTASI DENGAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) - Pujiastuti, Lise; Amin, Ruhul; Hariyanto, Hariyanto; Supriyatna, Adi; Christian, Ade; Sumanto, Sumanto (Journal of Innovation And Future Technology (IFTECH), 2024)
This study aims to evaluate the performance of lecturers in higher education using the Multi Attribute Utility Theory (MAUT) method. The main problem faced is the complexity of assessing lecturers based on the Tri Dharma of Higher Education-education, research, and community service-as well as the challenges of subjectivity and inefficiency in manual assessment. MAUT was chosen due to its ability to consider various assessment criteria in a structured and objective manner and follows the standardization of outstanding lecturer assessment including: Education, Research, Community Service, Discipline, Commitment, Cooperation Ability and Ability to innovate. The results showed that Adi Fajar Insani had the best performance with a total final score of 1.01, while Dian Eka Fitriani had the lowest score of 0.00. The MAUT method proved effective in providing a comprehensive and fair assessment, overcoming the limitations of traditional methods that are not thorough. The conclusion of this study is that the application of MAUT can improve the objectivity, efficiency, and accuracy of the lecturer evaluation process, thus encouraging the improvement of lecturer quality and productivity in various fields. Further research is recommended to develop more relevant assessment criteria, involve larger samples, and explore the use of more sophisticated technology to support the assessment process.